Abnormal Thyroid Function and Recurrent Pregnancy Loss - Shrestha, A; Chawla, CD (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The aim of our study was to observe the benefit of screening for thyroid function amongst women with recurrent pregnancy loss and effect of treatment for thyroid disorder on pregnancy outcome. Methods: This was a longitudinal study conducted from June 2012 to December 2013. One hundred and three patients with recurrent pregnancy loss without features of thyroid disorder were included. They were investigated for thyroid stimulating hormone (TSH), free tri iodothyronin (FT3), free thyroxine (FT4) levels and for auto-antibodies against thyroperoxidase (anti TPO). The patients with abnormal TSH levels were treated with thyroxine depending on the level of TSH. Results: TSH, FT3, FT4 and anti TPO levels were measured. Amongst 103 ladies, thirty-eight (36.89%) had high levels of TSH. Thirty-five (33.98%) of them underwent test for anti TPO, of which two (5.71%) had autoimmune thyroiditis. Nine (8.73%) out of 103 had high FT4 levels. Ladies with diagnosis of hypothyroidism underwent treatment and 17 (44.73%) out of 38 had conceived. Conclusions: Of 103 women with recurrent pregnancy loss, abnormal thyroid function was detected in 47. Seventeen (44.73%) of them with increased TSH level conceived after treatment with thyroxine, which gives a positive message that hypothyroidism is a treatable cause for recurrent pregnancy loss. DOI: http://dx.doi.org/10.3126/njog.v9i1.11184 NJOG 2014 Jan-Jun; 2(1):29-32